A Review of UWB MAC Protocols - Mohd Zin, Mohd Shahril Izuan (2010)
In this paper, we review several ultra-wideband (UWB) medium access control (MAC) protocols that have been proposed to date. This review then considers the possibility of developing an optimal MAC layer for high data rate UWB transmission systems that transmit very little power especially in application to mobile devices. MAC in UWB wireless networks is necessary to coordinate channel access among competing devices. Unique UWB characteristics offer great challenges and opportunities in effective UWB MAC design. We first present the background of UWB and the concept of MAC protocols for UWB. Secondly, we summarize four UWB MAC protocols that have been proposed by other researchers and finally, a conclusion with a view to the planned future work. The main contribution of this paper is that it presents a summarised version of several MAC protocols applicable to UWB systems. This will hopefully initiate further research and developments in UWB MAC protocol design.